2015
DOI: 10.3390/ijms16059431
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Salvage Deficiencies, DNA Damage and Neurodegeneration

Abstract: Nucleotide balance is critically important not only in replicating cells but also in quiescent cells. This is especially true in the nervous system, where there is a high demand for adenosine triphosphate (ATP) produced from mitochondria. Mitochondria are particularly prone to oxidative stress-associated DNA damage because nucleotide imbalance can lead to mitochondrial depletion due to low replication fidelity. Failure to maintain nucleotide balance due to genetic defects can result in infantile death; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 83 publications
0
67
0
Order By: Relevance
“…pools, is well established in patients carrying mutations in the thymidine kinase, thymidine phosphorylase, and deoxyguanosine kinase genes. 36,37 Despite the heterogeneity of this disease and the small size of the cohort, a robust metabolomics signature has been obtained. One limitation of our metabolomics analysis on plasma, while interesting in the sense that it gives a general view of the individual's conditions, is in fact not suitable to identify the organs that are responsible of the compounds' secretion contributing to the signature.…”
Section: Discussionmentioning
confidence: 99%
“…pools, is well established in patients carrying mutations in the thymidine kinase, thymidine phosphorylase, and deoxyguanosine kinase genes. 36,37 Despite the heterogeneity of this disease and the small size of the cohort, a robust metabolomics signature has been obtained. One limitation of our metabolomics analysis on plasma, while interesting in the sense that it gives a general view of the individual's conditions, is in fact not suitable to identify the organs that are responsible of the compounds' secretion contributing to the signature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that disruption of mitochondrial energy metabolism can cause an imbalance of ribonucleotides, which then contributes to neurodegeneration (Fasullo and Endres 2015; Nikkanen et al 2016). Deficient mitochondrial energy production makes Drosophila photoreceptors more vulnerable to light-induced degeneration and produces a visual defect in zebrafish (Taylor et al 2004; Jaiswal et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review focuses on the supportive and detrimental roles of P2Y receptors in neurodegeneration [18]. Another review considers nucleotide salvage deficiencies and DNA damage in neurodegenerative diseases [19]. A third review focuses on the neuromodulatory actions mediated by P2X…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%